illustrated classics the count of monte cristo - Dumas, Alexandre; Alexandre Dumas (India indiana publishing house, 2008)
The Count of Monte Cristo is a classic adventure novel by Alexandre Dumas about a young sailor, Edmond Dantès, who is falsely accused of treason and imprisoned for 14 years. After a daring escape, he uses a vast hidden treasure to reinvent himself as the wealthy and enigmatic Count of Monte Cristo to exact a cold, calculated revenge on the men who betrayed him.